Preliminary Experiment on the Effect of 18% Substitute Salt on Home Blood Pressure Variability in Hypertensives - Jing Li; Lisha Mu; Huakun Rao; Yangfeng Wu; Hao Wang; Hongbing Tao; Lihong Mu (International Journal of Hypertension)
At present, the effect of substitute salt in reducing sodium intake and blood pressure is relatively clear. The present study is a phase I clinical trial involving 43 hypertensives in which the effect of 18% sodium substitute salt on the home blood pressure variability (BPV) was observed for 8 weeks with weekly follow-up. Finally, 4 patients were lost, and 39 patients completed the intervention and were included in the analysis. Daily home blood pressure and weekly adverse events were collected. The systolic blood pressure (SBP) in the morning (−10.0 mmHg, 95% CI: −16.5 to −3.5, P = 0.003), SBP at night (−10.2 mmHg, 95% CI: −16.1 to −4.3, P = 0.001), and diastolic blood pressure (DBP) at night (−4.0 mmHg, 95% CI: −7.1 to −0.8, P = 0.014) decreased significantly. Also, there was no statistically significant change in morning (F = 1.137, P = 0.352) and night diastolic (F = 0.344, P = 0.481) BPV and morning systolic BPV (F = 0.663, P = 0.930) over time during the intervention period, except for that night systolic BPV had a downward trend (F = 2.778, P = 0.016) and had decreased 2.04 mmHg (95% CI: 0.84 to 3.23, P = 0.001) after intervention. The use of 18% of the substitute salt did not increase BPV during the intervention and even may decrease it, which indicates its control effects on blood pressure. This study is the first one to observe the effect of 18% sodium substitute salt on the home blood pressure variability, providing a basis for further experiments.